2008
DOI: 10.1038/ijo.2008.169
|View full text |Cite
|
Sign up to set email alerts
|

Negative association between plasma levels of adiponectin and polychlorinated biphenyl 153 in obese women under non-energy-restrictive regime

Abstract: The aim of this study was to reveal whether accumulation of the persistent organic pollutants (POPs), especially polychlorinated biphenyl (2,2 0 ,4,4 0 ,5,5 0 -hexachlorobiphenyl, PCB 153), affects plasma levels of adiponectin in obese patients. The study was designed as a longitudinal intervention trial with a control group, where 27 obese women (body mass index (BMI)430 kg/m 2 ; age 21-74 years) were studied before (OB) and after (OB-LCD) a 3-month low-calorie-diet intervention (LCD; 5 MJ daily). As the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
0
17
2
1
Order By: Relevance
“…In general, alterations in glucose and insulin metabolism due to PCBs and dioxins may be mediated by AhRs (Craft et al 2002, Everett et al 2011, Baker et al 2013. In contrast to the findings of the present study, a negative correlation has been found between adiponectin concentration and PCB 153 (Mullerova et al 2008) On the basis of these results, it is possible that the controversy about these markers may reflect the thyroid dysfunction due to PCB 95. Furthermore, data reported herein support a positive association between serum TNFa concentration and weaning exposure to PCB 95.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In general, alterations in glucose and insulin metabolism due to PCBs and dioxins may be mediated by AhRs (Craft et al 2002, Everett et al 2011, Baker et al 2013. In contrast to the findings of the present study, a negative correlation has been found between adiponectin concentration and PCB 153 (Mullerova et al 2008) On the basis of these results, it is possible that the controversy about these markers may reflect the thyroid dysfunction due to PCB 95. Furthermore, data reported herein support a positive association between serum TNFa concentration and weaning exposure to PCB 95.…”
Section: Discussioncontrasting
confidence: 99%
“…However, their effects and precise toxicological mechanism(s) during development remain unclear. On the other hand, in animal and human studies, PCBs have been shown to disrupt adiponectin (Mullerova et al 2008), leptin (Nieminen et al 2000), tumor necrosis factor (TNFa; Arsenescu et al 2008), and insulin (Everett et al 2011) concentrations, body weight, energy expenditure and fat depots (Anbalagan et al 2003). However, studies on possible interactions between PCBs and adipokine concentration changes associated with thyroid dysfunction during the early weaning period are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Few previous studies have examined the influence of organochlorines on development of obesity or changes in body composition, although these chemicals have been suspected as obesogens 27 due to their endocrine-disrupting properties in addition to an observed negative association between PCB 153 and the metabolismmodulating hormone, adiponectin. 28 A recent study reported that maternal serum DDE levels were associated with rapid infant weight gain and elevated 14-month BMI in their offspring. 29 Certainly, more research in adults is needed from longitudinal studies of the effects of these chemicals on weight gain and on patterns of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind this hypothesis is that alterations in the physiological regulation of hormones such as leptin, adiponectin and ghrelin could influence local metabolism and have broader effects on other metabolic parameters, including satiety, nutrient storage, energy expenditure and insulin sensitivity [116]. Indeed, sparse evidence has shown a negative association between POPs with adiponectin and leptin in obese patients [117][118][119].…”
Section: Hormonal Disturbancesmentioning
confidence: 99%